Association between the presence of brown adipose tissue and non-alcoholic fatty liver disease in adult humans - TUROĞLU, HALİL TURGUT; ATUĞ, ÖZLEN; ÖZGÜVEN, SALİH; ÖNEŞ, TUNÇ; YILMAZ, YUSUF (WILEY-BLACKWELL, 2011)
Background The presence of active brown adipose tissue (BAT) has been associated with a reduced risk of obesity in adult humans. Aim To examine whether the presence and activity of BAT in patients undergoing PET-CT examinations is related to the presence of fatty liver. Method We retrospectively analysed 3666 consecutive PET-CT whole-body scans performed on a total of 1832 patients who were referred for suspected malignancies. BAT-positive subjects (BAT+) were defined as subjects who showed substantial amounts of brown adipose tissue on PET-CT scans. In areas where uptake of [F-18] FDG was identified by CT for BAT, the maximal standardised uptake values (SUVmax), defined as the maximum activity per millilitre within the region of interest divided by the injected dose in megabecquerels per gram of body weight, were determined. A ratio of mean liver attenuation to spleen attenuation <0.8 on CT scans was considered to indicate NAFLD. Results Thirty patients of the 1832 screened individuals (2%) demonstrated brown fat uptake (BAT+ subjects). Ninety matched individuals without evidence of BAT on PET scans (BAT) subjects) were enrolled for comparison purposes. After adjustment for potential confounders, the odds ratio for having NAFLD was significantly higher for BAT) subjects (3.12, 95% confidence interval = 1.03-9.88, P < 0.05). The SUVmax for brown fat tissue was significantly correlated with the ratio of mean liver attenuation to spleen attenuation (P < 0.05). Conclusion The presence of brown adipose tissue in adulthood is independently associated with a lower likelihood of NAFLD diagnosed by CT findings.
Keywords: INSULIN-RESISTANCE; HEPATIC STEATOSIS; DIAGNOSIS; STEATOHEPATITIS; ARTICLE; SEX; AGE